Rethinking Art and Visual Culture - Grønstad, Asbjørn Skarsvåg. author. aut Link
IX, 196 p. 6 illus., 5 illus. in color.
Keywords: This is the first book to offer a systematic account of the concept of opacity in the aesthetic field. Engaging with works by Ernie Gehr, John Akomfrah, Matt Saunders, David Lynch, Trevor Paglen, Zach Blas, and Low, the study considers the cultural, epistemological, and ethical values of images and sounds that are fuzzy, indeterminate, distorted, degraded, or otherwise indistinct. Rethinking Art and Visual Culture shows how opaque forms of art address problems of mediation, knowledge, and information. It also intervenes in current debates about new systems of visibility and surveillance by explaining how indefinite art provides a critique of the positivist drive behind these regimes. A timely contribution to media theory, cinema studies, American studies, and aesthetics, the book presents a novel and extensive analysis of the politics of transparency.